Implementation of the Blended Learning Method on Student Learning Motivation in History Class X IIS at SMA Labschool Untad Palu in the New-Normal Period - Ika Nur Jayanti; Herlina; Juraid Abdul Latief; Iskandar; Suyuti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aims to analyze the implementation of the Blended learning method in history subjects on students' learning motivation in the learning process in class X IIS SMA Labschool Untad Palu and to analyze the role of the Blended Learning method in increasing student motivation in history subjects in the learning process in class X IIS Labschool Untad Palu High School. This research is a qualitative study which took place at Labschool Untad Palu High School, Palu City, Central Sulawesi. The subjects of this study were all students of class X IIS at SMA Labschool Untad Palu with a total of 1 class and 23 students, as well as history teachers who teach at SMA Labschool Untad Palu. Data collection techniques using observation, interviews and documentation. Data processing techniques are descriptive qualitative. The results showed that the implementation of the Blended Learning method in history subjects on student learning motivation in the learning process in class X IIS SMA Labschool Untad Palu was the learning process carried out in 5 working days, 4 working days carried out face-to-face in class and 1 day carried out face-to-face online or online. The application of the Blended Learning method can increase student learning motivation, especially in class X IIS SMA Labschool Untad Palu. This can be seen from the successful achievement of the seven indicators of the Blended Learning method and the increase in the average score of students' history subjects from 87.24 to 89.45. The role of the Blended Learning method in increasing student motivation in history subjects in the learning process in class X IIS SMA Labschool Untad Palu is very important and can give a special impression to students.